Parents\' parenting styles with perfection in single-parent families and several children - Nourolah Taheri; Razieh shirzadegan; Saeideh Elhami; Nahid Mahmoudi; Maryam Ban; Sara Sarvandian (Kurdistan University of Medical Sciences, 2017)
Background & Aim:  It is an effective way to nurture healthy people in the family education community and to provide parents with information. The aim of this study was to investigate the relationship between parental parenting styles and perfectionism in nursing and medical students of the Faculty of Medical Sciences of Abadan and its comparison with single-parent families and several children in 2014. Materials & Methods: This is a a descriptive-analytic approach. The study population consisted of 322 nursing and medical students who entered the study by simple random sampling. Demographic questionnaire, parenting styles questionnaire and perfectionism questionnaire were used to collect information. Results: There is no meaningful difference in men in the 4 dimensions of perfectionism (doubts about actions, parental expectations, parental criticism and ordering) between children and children, but worries about mistakes with a child are greater than worries about mistakes. With several children (P<0.05). The most influential child-rearing style in both sexes is male and female. In men, there is a positive and significant relationship between the authoritative parenting style and order. (P<0.01, r=0/68) And there is the least statistical relation between this parenting style and parental criticism (P<0.01, r=-0/37). Conclusion: Considering the abnormal structure of perfectionism, the recognition of the relationship between parental parenting styles and the perfectionism of children, in addition to advancing perfectionism and personality theories, has helped educators to apply in practice with education Appropriate childcare practices prevented the development of this structure to some extent.